Prevalence of Gardnerella vaginalis and Atopobium vaginae in Portuguese women and association with risk factors for bacterial vaginosis - Silva, Débora (2014)
Among Portuguese women, there was a high correlation between biofilm-forming Gardnerella vaginalis and Atopobium vaginae colonization associated to BV.